Zakład Myśli Ekonomicznej - Kundera, Janina Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The history of economic thought was taught at the Faculty of Law since 1945, and the research in this field was begun by Prof. Wincenty Styś. In 1990 the Department of Economic Thought in the Institute of Economic Sciences was established. Since 1998 it is headed by Prof. Elżbieta Kundera. The area of research includes socioeconomic thought in Germany of the 19th century, doctrines of welfare state, Polish economic thought of the interwar period and the directions of alternative economics. The most important achievements are the monographs: E. Kundera, Ferdinand Lassalle 1825–1864, Doktryna „socjalizmu z katedry” 1872–1918 [The Doctrine of “Socialism from the pulpit” 1872–1918], E. Kowalczyk, Poglądy ekonomiczne i polityczne Wincentego Stysia [Economic and Political Views of Vincent Styś] 2013, and Słownik historii myśli ekonomicznej [Dictionary of the History of Economic Thought] ed. E. Kundera 2004, 2014.
Keywords: Zakład Myśli Ekonomicznej; Wydział Prawa Administracji Ekonomii UWr; history